An Examination of the Role of Leaders in Sustaining Academic Integrity During Online Assessments in Five of Sharjah Schools During COVID-19 - HAMAD, HANAN AHMAD (2023)
The purpose of this study is to investigate the main impediments that jeopardize reliable online assessment data since the outbreak of COVID 19 pandemic, as well as the measures employed by leaders to mitigate these obstacles and maintain academic honesty, such as policymaking and ensuring the effective application of updated assessment policies. Authentic leadership theory lay the basis of this study and connections are explained thoroughly. The Fraud triangle Model extrapolates the process of misconduct by explaining the relation between motives, opportunity and academic misconduct. Main concepts such as academic integrity and online assessments are defined and analysed. A mixed method approach is used, which includes a survey of thirty school leaders in five schools in Sharjah, UAE, a semi-structured interview of 5 leaders, and an analysis of assessment policies in these schools. The findings are examined and compared to help provide a clear understanding of the research objectives. Findings show a clear misalignment between leaders’ responses and assessment policy documents which provides an insight of improper implementation of these policies. It was also clear that these policies were neither updated nor assessed. It is also clear that due to dominant beliefs among parents and students about the significance of marks, parents tend to participate in dishonest behaviour whether intentionally or not. Other threats to credibility of online assessment results include ease of access to resources and assistance during the test, whether from peers, parents or tutors. Based on the feedback from participants, numerous recommendations are made to assist administrators, school administrators, and decision makers in enhancing future online assessment methods. In conclusion, it is perceived based on data analysis that no matter how preventative and punitive measures school leaders take, the first deterrent to academic misconduct is the culture of integrity and the extent people believe in the worth of this value.